Life-Cycle Assessment of Sector-Coupled National Energy Systems: Environmental Impacts of Electricity, Heat, and Transportation in Germany Till 2050 - Baumgärtner, Nils; Deutz, Sarah; Reinert, Christiane; Nolzen, Niklas; Kuepper, Lucas Elias; Hennen, Maike; Hollermann, Dinah Elena; Bardow, André (Frontiers in Energy Research, 2021)
National energy models models are used to provide decarbonization strategies. Most national energy models focus on costs and greenhouse gas emissions only. However, this focus carries the risk that burdens shift to other environmental impacts. Energy models have therefore been extended by life-cycle assessment. Deep decarbonization is only possible by targeting all high-emission sectors. Thus, we present SecMOD, a holistic national energy model that includes high-emission sectors and life-cycle assessment. SecMOD accounts for electricity, residential and industrial heat, as well as private transportation. The linear optimization model computes a cost-optimal transition path towards an energy system satisfying given greenhouse gas reduction targets. A two-step decomposition approach allows computing solutions with hourly time resolution efficiently. By integrating full life-cycle inventories for energy technologies, the model provides detailed environmental impacts for electricity, heat, and transport processes in Germany up to the year 2050. Our results show that thermal insulation in the building sector, renewable energies and storage are key echnologies for decarbonized energy systems. Further, sector-coupling by electrification is crucial, which doubles the electricity demand in the year 2050. Our life-cycle assessment shows that environmental impacts shift from operation to infrastructure, highlighting the importance of an impact assessment over the full life cycle. For example, a reduction of 80 % in operational greenhouse gas emissions corresponds only to a total reduction of 70 % over the full life cycle. Decarbonization leads to many environmental co-benefits. However, 5 out of 16 impacts increase, of which freshwater ecotoxicity and depletion of metal and mineral resources worsen the most. Thus, to avoid burden-shifting, holistic planning of decarbonization strategies should also consider other environmental impacts.